Communication Strategies Used by EFL Learners with Different English Achievements in Oral Communication - Anggit Prasetio Nugroho (Center of Language and Cultural Studies [CLCS], 2019)
This article aims to identify the communication strategies used by the learners with low and high English achievement in classroom oral communication and to describe the difference of the frequency of using communication strategies from low and high achievement learners. This research used a descriptive research. The researcher used a case-study design because the present research concentrated on communication strategies used by the learners with low and high English achievement in a specific setting. The 30 learners of the eleventh-grade learners at SMA Negeri 1 Malang was selected as research subject. The result showed that the learners employed 14 communication strategies. The mostly used by the learners was time-gaining strategy and followed by self-repetition, self-repair, appeal for help, code-switching, circumlocution, approximation, use of all-purpose word, other-repetition, message abandonment, other correction, topic avoidance, use of non-linguistic mean, and literal translation. This research also found that the learners with low English achievement used communication strategies more frequently than the learners with high achievement.